Enhanced electrochemical performance of solid PEO/LiClO4 electrolytes with a 3D porous Li6.28La3Zr2Al0.24O12 network - Fu, Xuelian; Li, Yuchao; Liao, Chengzhu; Gong, Weiping; Yang, Mingyang; Li, Robert Kwok Yiu; Tjong, Sie Chin; Lu, Zhouguang (Composites science and technology, 2019)
Low ionic conductivity and large interfacial impedance between the electrode and electrolyte are the main bottleneck issues of the current solid electrolytes. In this study, a novel 3D hierarchical solid electrolyte was developed to tackle the large interfacial impedance problem. A flexible polyethylene oxide/lithium chlorate (PEO/LiClO4) was in-situ formed inside the 3D porous Li6.28La3Zr2Al0.24O12 (LLZAO) network by simply using a cleanroom wiper as the template. The obtained 3D LLZAO-PEO/LiClO4 composite solid electrolyte exhibited a high ionic conductivity of 2.25 × 10−5 S cm−1 at 30 °C, being 30.7 times higher than that of pristine PEO/LiClO4 electrolyte. The improved ionic conductivity was attributed to the 3D porous LLZAO structure with continuous fast ion transport pathways. In addition, the 3D LLZAO network can effectively inhibited the growth of lithium dendrite, leading to excellent stability and desirable safety during lithium stripping/plating cycling. Furthermore, the all-solid-state LiFePO4/Li battery system based on the obtained 3D LLZAO-PEO/LiClO4 electrolyte showed a high initial discharge specific capacity of 143.8 mAh·g−1 and a high capacity retention of 86% after 200 cycles at 60 °C. This 3D composite solid electrolyte design is very effective in reducing the interfacial impedance and provides a solution for the further development of high-performance solid electrolyte for all-solid-state rechargeable batteries.